The Socialization of Technology Education in Supporting the Health Sector Among SMA/SMK/SLB Students in Regional Branch Office 2 of North Sumatra and Its Influence on Higher Education Choices - Bhakti Alamsyah; Siti Aisyah; Meyga Fitri Handayani Nasution (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the effect of health-oriented technology education socialization programs on the higher education choices of SMA/SMK/SLB students under the Regional Branch Office 2 of the North Sumatra Provincial Education Office. A mixed-methods design was employed, integrating quantitative surveys and qualitative interviews. The research sample consisted of 342 Grade XI and XII students from 18 schools (10 SMA, 6 SMK, and 2 SLB) across Deli Serdang Regency, Serdang Bedagai Regency, and Tebing Tinggi City. Data were gathered through structured questionnaires, Focus Group Discussions (FGD), and direct observation during socialization events. Quantitative analysis used logistic regression and chi-square tests, while qualitative data were analyzed thematically. Findings reveal that 67.8% of students experienced a significant shift in interest toward health technology study programs following socialization. The intensity of socialization exposure was statistically associated with students' decisions to pursue health technology-related degrees (OR = 3.47; 95% CI: 2.18–5.52; p < 0.001). Given the absence of a control group, this finding indicates an association rather than definitive causal evidence. Key contributing factors included the quality of socialization materials, relevance to local healthcare industry needs, and scholarship information availability. This study recommends strengthening technology-based socialization programs across all secondary education units to support the supply of technology-competent health workers in North Sumatra.